ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR DI KANTOR BERSAMA SAMSAT TABANAN - Putra, I Made Adi Darma; Jati, I Ketut (E-Jurnal Akuntansi; Vol 18 No 1 (2017), 2017)
This research aimed to get empirical evidence about the influence of taxpayer awareness, moral obligation, tax knowledge and perceptions about tax penalties on waijb tax compliance in paying motor vehicle tax (PKB) in the Office of the Joint SAMSAT Tabanan. The theory used in this research is the Theory of Planned Behavior. The population in this research are all taxpayers motor vehicle registered in the Office of the Joint SAMSAT Tabanan until 2015 that as many as 351.829 taxpayers. The samples used in this study were 100 taxpayers with sampling technique accidental sampling method. The data collection was conducted by questionnaire. Data analysis technique used is multiple linear regression analysis. The results showed that awareness of the taxpayer, a moral obligation, tax knowledge and perceptions about tax penalties have positive impact on taxpayer compliance in paying motor vehicle tax (PKB) in the Office of the Joint SAMSAT Tabanan.
Keywords: taxpayer awareness; moral obligation; tax knowledge; perception of tax penalties; tax compliance